Synthesis, Characterization and Determination Antioxidant Activities for New Azo Dyederived from Sulfamethoxazole and Some Metal Ion Complexes - Mahdi Abdullah, Amnah; Salih Al-Hamdani, Abbas Ali; Wail Al Zoubi (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Diazotization reaction between 1-(2,4,6-trihydroxy-phenyl)-ethanone and diazonium salts produced the ligand 4-(3-Acetyl-2,4,6-trihydroxy-phenylazo)-N-(5-methyl-isoxazol-3-yl)-benzenesulfonamide, which in turn reacted with the metal ions (Ni2+, Zn2+, Pd2+ and Pt4+) forming stable complexes with Octahedral geometry suggest of (Ni2+ and Pt4+), Zn2+ complex Tetrahedral and Pd2+ complex Square planer. The creation of such complexes was detected by employing spectroscopic means involving ultraviolet-visible, which proved the obtained geometries; FT-IR confirmed the formation of the azo group and the coordination with metal ions through it. Thermogravimetric analysis studies demonstrated the coordination of water residues (aqua or hydrate) with metal ions inside the coordination sphere, as well as used curve DSC to calculate the thermodynamic parameters ΔH, ΔS, and ΔG. Moreover, element microanalysis and atomic absorption gave corresponding outcomes with theoretically counting outcomes. Neuclearmagnatic resonances for 1H and 13C, chlorine atoms, and magnetic moment quantifications also indicate the formation of azo dye ligand. The ligand and new complexes showed antioxidant abilities to scavenge free radicals.